PEMBUKTIAN TINDAK PIDANA PENISTAAN AGAMA BERDASARKAN VIDEO DI MEDIA SOSIAL MENURUT PASAL 27 AYAT (3) UNDANG-UNDANGN NO 19 TAHUN 2016 ATAS PERUBAHAN UNDANG-UNDANG NO 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELETRONIK ( ITE ) - Muhammad Fathur Rahman (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractThe development of technological advances making it easier for one to access social media and bias to create a status of both writing, drawing, and video. Seiringngya with such facilities is also in the same manner of crimes in social media, one of the many circulating writings, images, or videos that violate the provisions of the invitation in the Republic of Indonesia.So that the religion that notabenenya as a person's spiritual identity becomes the target of blasphemy by a person who is not responsible and make a community as a citizen of the Republic of Indonesia, which the country guarantees freedom in the religion that is believed to be religious. There are 6 recognized religions in the country Republic Indonesia, including religion of Islam, Catholicism, Christianity, Hinduism, Buddhism, and religious religions. And the religion that is widely adopted in the Republic of Indonesia is the Islamic religion.Based on the results of research and discussion, it can be concluded that the cause of religious blasphemy crimes is the failure of the development of religion, weak law enforcement, the emergence of the defenders of religious taking, the media is not the party to the religion that is denied. Thus making the opportunity of a person whose crisis of religious sciences easily blasphemy the religion. In the end, based on the above conclusion, the author's suggestion needs to spread religion or even wider da'wah so that all religious teachings can be conveyed well and can be understood every adherence. To put a religious position above everything than a need for strict sanction of the law enforcement officers for religious conners. So it becomes one of the right means of creating justice.Keyword: criminological Penista religious social media